Pelatihan Pembuatan Naget Ikan Lele (Clariidae) Di SMK Taruna Kelautan Dan Perikanan Kota Bengkulu - Munhedy Vierzhen; Rabiul Armala Sari Nande Putri; Ifan Tarmoro; Rida Fahmi; Evi Andriani (Jurnal Dehasen Untuk Negeri, 2023)
The abundance of catfish harvests often makes the selling price of catfish low. Therefore, to utilize catfish, new innovations are needed so that it becomes a catfish product that has high economic value and long shelf life. Processed food products from catfish, which have the potential to be developed into products of economic value, are processed catfish nuggets. diversification of fish processing products. This activity is expected to provide benefits for students to increase knowledge, skills and be able to think creatively and innovatively based on entrepreneurship in processing fishery products. The training activity for making catfish nuggets was carried out at the Pondok Kubang Marine and Fisheries Vocational School, Bengkulu City. Participants in this activity were 25 students of Marine and Fisheries Vocational High School. This activity was carried out for 10 (ten) days, from March 17 2022 to March 26 2022. The training activities for making catfish nuggets are: preparation of tools and materials, weighing of materials, sorting, grinding, mixing of ingredients, steaming, cutting, blanching , freezing, frying and packaging